Anthologists and the literary market: a comparative study of al-Thaʿālibī’s Yatīmat al-dahr and ʿAwfī’s Lubāb al-albāb - White, J (2018)
This thesis offers the first detailed study of publishing culture in the medieval eastern Islamic world by examining how two influential anthologists active in Central Asia mediated between authors and their audiences. It analyses the contents of al-Thaʿālibī’s (d. 429/1037-8) Yatīmat al-dahr, a biographical anthology of Arabic poetry and prose concerned with the literature of the 4th/10th and the early 5th/11th centuries, comparing them with the material found in ʿAwfī’s (d. 640/1242 or before) Lubāb al-albāb, a biographical anthology of Persian poetry focused on verse produced between the late 3rd/9th and the early 7th/13th centuries. Yatīmat al-dahr and Lubāb al-albāb are approached as ventures which aimed to render the high culture of Arabic and Persian literature accessible to readers by presenting hitherto unpublished texts in a pedagogical fashion. The thesis contributes to a current wave of research that is concerned with the history of the book in the Islamic world, but it moves the focus of such scholarship onto literary texts and their manipulation. Its principal findings can be summarised as follows: Firstly, it revises the prevalent idea that literary culture was entirely dependent on patronage, by demonstrating how market demand influenced the kinds of writing produced in the different regions of the Arabic- and Persian-speaking worlds. Patronage emerges as a force that was intertwined with the book trade, which had already begun to define conceptions of authorship. Secondly, it shows that anthologies are more than collections of exemplary texts, by uncovering how al-Thaʿālibī and ʿAwfī pursue the study of society, literary history and literary theory. The anthologists did not simply reproduce extracts, but edited them in accordance with their broader intellectual projects. Lastly, it reconstructs the cosmopolitan literary culture which existed in Khurasan and Transoxiana between the 4th/10th and 7th/13th centuries, showing that many authors worked in bilingual Arabic-Persian environments, moved between Arabic and Persian spheres, and read books in both languages. The thesis is accompanied by an index of circa eight thousand poems catalogued by genre, and by an appendix which lists the material that the anthologists drew from their sources.